2020
DOI: 10.2139/ssrn.3547729
|View full text |Cite
|
Sign up to set email alerts
|

The Global Macroeconomic Impacts of COVID-19: Seven Scenarios

Abstract: The outbreak of coronavirus named COVID-19 has disrupted the Chinese economy and is spreading globally. The evolution of the disease and its economic impact is highly uncertain which makes it difficult for policymakers to formulate an appropriate macroeconomic policy response. In order to better understand possible economic outcomes, this paper explores seven different scenarios of how COVID-19 might evolve in the coming year using a modelling technique developed by Lee and McKibbin (2003) and extended by Mc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
918
1
58

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,167 publications
(992 citation statements)
references
References 19 publications
(19 reference statements)
15
918
1
58
Order By: Relevance
“…Over the following months the resulting disease, subsequently named COVID-19, spread across the rest of the world and was declared a pandemic by the World Health Organization on March 11th, 2020. As of submission, there are over 2.2M reported infections worldwide and over 150,000 reported deaths, with an anticipated world wide death toll in the millions and an economic impact sufficient to cause a worldwide recession or depression 1,2 . There are currently no vaccines available and the only available therapies are supportive or based largely on anecdotal work.…”
mentioning
confidence: 99%
“…Over the following months the resulting disease, subsequently named COVID-19, spread across the rest of the world and was declared a pandemic by the World Health Organization on March 11th, 2020. As of submission, there are over 2.2M reported infections worldwide and over 150,000 reported deaths, with an anticipated world wide death toll in the millions and an economic impact sufficient to cause a worldwide recession or depression 1,2 . There are currently no vaccines available and the only available therapies are supportive or based largely on anecdotal work.…”
mentioning
confidence: 99%
“…Going by the present trends, the cases are likely to increase in the near future (Vellingiri et al, 2020). This is going to place a huge economic burden, especially on developing and underdeveloped countries (McKibbin and Fernando, 2020).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…This stringent action is not without a cost to society. It has a major social and economic disruptions [11][12]. The uncertainties related to the outbreak also creates anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…A study showed if we lift the suppressive measure too early, the massive outbreak may recur. On the contrary, if the measure was in place for too long, the social, economic, and psychological effect will be massive [12].…”
Section: Introductionmentioning
confidence: 99%